Current findings from research on professional librarian skills development and needs in Brazil - Paletta, Francisco Carlos; Milanesi, Luis (Informação & Sociedade, 2016)
This paper presents reflections on the outcome of a research project conducted at the School of Communications and Arts of the University of São Paulo, regarding librarian training, their field of expertise and the need for continued education. The methodological design compiled in the research project involved planning-presenting project, and developing the questionnaire for data collection. The electronic form was applied to an intentionally random, stratified sample of 18,374 active librarians throughout Brazil, totalling 3,320 responses that were statistically treated and compiled. Once the data was collected using the electronic forms, we analysed the collected information and the literature, cleansed the information and standardized the bibliographic records and statistical processing of data that formed the results presented in this research project. As the world gets more sophisticated and diversified, the competence required of the professional librarian, which in a first stage is highly technical – remembering that it is impossible to dispose of or move forward without it being well established – grows and includes other important responsibilities in the new organizational environment. We must work towards a holistic qualification, valuing management, methodological, cultural, multidisciplinary and systemic skills – all highlighted in the economy of knowledge.